PENGARUH IMPLEMENTASI SISTEM MANAJEMEN LINGKUNGAN, AKUNTANSI LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Mega Amelia (2017)
This study was conducted to examine the effect of implementation environmental management system, environmental accounting and environmental performace on financial performance at the Company's mining, energy and oil & gas listed in Indonesia Stock Exchange during the year 2014-2016. The population used in this study amounted to 49 mining, energy and oil & gas companies listed in Indonesia Stock Exchange 2014-2016. The sample obtained in this study amounted to 10 samples are selected using content analysis method and purposive sampling which partisipation on PROPER and published its financial statements and annual report as well as the complete data related to the variables used. Data were tested using Multiple Linear Regression Analysis with SPSS 23 and a significance level of 5%. The results of the testing showed that: (1) implementation of an environmental management system does not have a significant impact on the financial performance because it has a significance level 0f 0,099 is greater than the specified level α = 0,05. (2) implementation of an environmental accounting does not have a significant impact on the financial performance because it has a significance level 0f 0,821, is greater than the specified level α = 0,05. 3) environmental performance does not have a significant impact on the financial performance because it has a significance level 0f 0,332 is greater than the specified level α = 0,05.